Associations of the edge: Arctic imaginaries. Issue 3 (27th May 2019) - Lehtinen, Ari Aukusti
ABSTRACT: The article analyses the most recent environmental debate on Arctic warming. Three main concerns are identified. First, the debate underlines that the ongoing Arctic change is a warning of the planetary crisis to come. Second, it emphasises that this change is a symptom of epochal transition toward the Anthropocene. Third, it regards the change as an outcome of the continuing colonial repression of the extreme North. The main objective of the study on which the article is based was to evaluate these concerns as part of the main historical imaginaries of the Arctic (singled out from related literature). The method utilised was an application of 'critical reading' developed by post-colonial researchers. The evaluation revealed that in order to strengthen their message, environmentalists have creatively utilised and developed ancient imaginaries of the Arctic. However, at times, this coupling has in practice resulted in conceptual associations that weaken the environmentalists' potential in formulating foundational critiques and alternatives. The evaluation of the environmental concerns also helped to sketch the contours of an Arctic development alternative that is grounded on reciprocal localisation and ethno-ecological cooperation.